TANGGUNGJAWAB MASKAPAI ATAS GANTI KERUGIAN IMMATERIL PADA PERKARA WANPRESTASI AKIBAT PEMBATALAN JADWAL PENERBANGAN (Studi Kasus Putusan MA NO. 2822K/PDT/2014 Tanggal 28 Agustus 2015) - Soraya, Nada Intan (Universitas Muhammadiyah Ponorogo, 2024)
This study aims to analyze the form of airline responsibility in providing immaterial compensation to passengers due to flight schedule cancellations categorized as default. The focus of this study is to understand the legal basis, the form of compensation that can be given, and the application of the law based on the Supreme Court's decision case Number 2822k/Pdt/2014 dated August 28, 2015. In this case, the airline PT. Lion Mentari Airlines was required to pay immaterial compensation of Rp. 50,000,000 to the plaintiff. The research method used is doctrinal legal research with a normative juridical approach. Data collection was carried out through library research with primary legal sources such as the Civil Code (KUH Perdata) and secondary legal sources in the form of literature, journals, and relevant legal documents. Data were analyzed qualitatively to gain a deep understanding of the application of the law related to airline responsibility in cases of default. The results of the study indicate that the airline's responsibility in providing immaterial compensation is based on the provisions of Article 1243 to Article 1252 of the Civil Code regarding breach of contract, as well as Article 1365 of the Civil Code regarding unlawful acts. The Supreme Court's decision in the case emphasizes the importance of respecting consumer rights and implementing the principle of justice in legal protection for injured passengers. These findings contribute to the development of consumer protection law in the air transportation sector in Indonesia.